PENERAPAN PEMBELAJARAN AKTIF DENGAN METODE DISKUSI UNTUK MENINGKATKAN PRESTASI SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM POKOK PEMBAHASAN MENGENAL IBADAH PADA BULAN RAMADHAN DI KELAS VI SDN SUMBERSARI 04 SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - Jannah, Nastiti Nurul; Walid, Muhammad; Zuhroh, Ni'matuz (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
ABSTRACT This research is based on the problem of (a) How can the application of the discussion method in the Islamic Religious Education (PAI) subject, the topic of discussion about Getting to Know Worship in the Month of Ramadan, improve student learning achievement in Class VI SDN Sumbersari 04 Odd Semester 2022/2023 Academic Year? Meanwhile, the aim of this research is to determine the application of the discussion method in the subject of Islamic Religious Education (PAI), the main topic of discussion about Getting to Know Worship in the Month of Ramadhan can improve student learning achievement in Class VI SDN Sumbersari 04 Odd Semester 2022/2023 Academic Year. Each round consists of four stages, namely: Planning, Action, observation and reflection. The target of this research is class VI students for the 2022-2023 academic year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that the low results of the Islamic Religious Education test at SDN Sumbersari 04 is a challenge for educators to improve the quality of education at SDN Sumbersari 04. Therefore, the author is interested in conducting research related to discussion methods in the subject of Islamic Religious Education ( PAI) which the author formulated in the title